Microorganisms Isolated From Foot Ulcers Infection Of Diabetic Iraqi Patients. - Ryath shaya AL-Hemedawi; Suhaila M. AL-Salloum; Saad S. AL-Azawi (مجلة كلية الطب, 2006)
Background: - Diabetic foot infections may be classified as superficial or deep. Bacteria are liable to enter any cut or ulcer causing infection. Defect in treatment of infected deep diabetic foot may result in oesteomyelitis, limb loss, and even death. Methods: - Microorganisms were isolated and identified from both superficial & deep foot ulcers infection of (60) diabetic patients. Results: - The present results showed that high incidence (30.8%) of Escherichia coli (E-coli) was isolated from dry - superficial foot ulcers followed respectively by Staphylococcus epidermidis (S. epidermidis). 3.1 % and 15.4% of Proteus mirabilis (P. mirabilis), equal Percentages for Klebsiellae Pneumoniae (K. pneumoniae), Klebsiellae ozaenae (K. ozaenae), Citrobacter freundii (C. freundii) and Pseudomonas aeruginosa (Ps. aeruginosa which were 7.7 %. the most common microorganisms isolated from wet - superficial foot ulcers were 14.3% of S. aurous and S. epidermidis, followed by equal by Percentages of E-coli, Enterobacter cloacae (E cloacae) k. pneumoniae, C. freundii; which were 9.5 % also equal Percentages for K. ozaenae, P. mirabilis, Morganella morganii (M. morganii) providencia rettgri (P. rettgri), Enterobacter. aerogenes (E. aerogenes), Acinetobacter baumanii (A. baumanii) & Ps. aeruginosa (4.8%) were isolated The present findings demonstrated that the microorganisms isolated from different depth of deep ulcer were 18.4% of Ps. aeruginosa, followed by equal Percentages (12.2%) of E-coli & P. mirabilis. Then 10.2% of k. Pneumoniae and equal Percentages 8.2% for both S. aureus& S. epidermidis, similar Percentages4.1 for Klebsiellae terrigina (K. terrigina) & providencia stuartii (p. stuartii). the other species from different other genera represent one (2.1 %) isolate only. Conclusions:- The infected superficial ulcers from diabetic patients demonstrates high incidence of Ecoli followed by S. epidermidis, Proteus and Klebsiella. While the most common microorganisms isolated from wet-superficial foot ulcers were S. aureus, S. epidermidis, E.coli, Enterobacter, Klebsiella, Proteus, Providencia, Morganella, Citrobeacter, Acinetobacter & pseudomonas. The microorganisms isolated from different depth of deep ulcers were pseudomonas, E.coli, Proteus, Klebsiella, S. aureus, S. epidermidis, S.capitis, Streptococcus viridans, Shigella, Serretia, Acinetobacter.